2018
DOI: 10.3390/nu10101394
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Dietary and Cognitive Intervention in 3–5-Year-Old Children in Indonesia: A Randomized Controlled Trial

Abstract: Early childhood nutritional interventions typically combine nutritional and psychosocial stimulation. Such combined interventions result in long-lasting improvements of cognitive abilities in children who are malnourished. Here, we investigated potential cognitive abilities in normally developing children in Indonesia who were, however, at risk for suboptimal cognitive development due to little psychosocial stimulation in their home environment. In a randomized controlled intervention, children of the experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…Beside sociodemographic factors, we found that the subscales from the HOME inventory contributed to the children’s cognitive performance, namely, the availability of learning materials at home, variety in daily stimulation, and parental responsiveness. These factors agree with several studies that also indicated that home environment had a significant correlation with children’s cognitive performance [15,3942]. A longitudinal study of American children from birth to school age found that cognitive stimulation at home was more effective in increasing children’s learning abilities in their early childhood than the stimulation found in primary school [41].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Beside sociodemographic factors, we found that the subscales from the HOME inventory contributed to the children’s cognitive performance, namely, the availability of learning materials at home, variety in daily stimulation, and parental responsiveness. These factors agree with several studies that also indicated that home environment had a significant correlation with children’s cognitive performance [15,3942]. A longitudinal study of American children from birth to school age found that cognitive stimulation at home was more effective in increasing children’s learning abilities in their early childhood than the stimulation found in primary school [41].…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, the composite index scores for WMI, PSI, and CPI in the WPPSI IV are based on the United States norm as no Malaysian norm is available. However, the WPPSI IV has been used in other Asian countries including Indonesia [39] and Pakistan [52]. Future studies should develop a Malaysian norm for the WPPSI IV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with previous studies showing a positive correlation between stimulation and children's cognitive function. 13,20,25,28 The percentage difference in cognitive function between the normal-height and short-stature groups was not significant. This finding was likely because in which most preschoolers received medium-level stimulation.…”
Section: Discussionmentioning
confidence: 86%
“…A randomized controlled trial on healthy children in Jakarta showed that a combination of cognitive stimulation and nutritional supplementation in early childhood was an effective intervention to improve global cognitive function. 13 Short stature is a linear growth failure that often occurs in early childhood. Stunted growth is short stature mainly due to a lack of nutritional intake and/ or recurrent infections, rather than genetic factors.…”
mentioning
confidence: 99%